Heavy Metals in Water and Sediments and Their Impact on Water Quality in Andean Micro-watersheds: A Study of the Colorado and Alajua Rivers in the Ambato River Watershed, Tungurahua, Ecuador - Rodny Peñafiel, Fabián Rodrigo Morales-Fiallos, Bolivar Paredes-Beltran, Dilon Moya, Adriana Jacqueline Frias Carrion and Belén Moreano (Nature Environment and Pollution Technology)
The present study aims to characterize the water and sediment quality of the Colorado and Alajua rivers within Ecuador’s Ambato River watershed, with a specific focus on the presence of heavy metals. Measurements were conducted at five sampling points along the upper and lower zones of each river, where both physicochemical and microbiological parameters, as well as concentrations of heavy metals in water and sediments, were analyzed. Most parameters exhibited statistically significant differences, as determined by the analysis of variance (ANOVA), between the values observed in the upper and lower zones of the micro-watersheds. Water quality in the mentioned rivers was assessed using specific water quality indices, WQI, namely the NSF-WQI and Dinius WQI. Additionally, the impact of heavy metal presence in the water and sediments was evaluated using the Heavy Metal Evaluation Index (HEI). While most parameters met the Ecuadorian quality standards for water sources intended for human consumption, concerns emerged regarding elevated levels of total and fecal coliforms along both rivers, which could limit the suitability of these rivers as a water source for human use and consumption. At various sampling points, water quality criteria for the preservation of aquatic life were not met for several heavy metals. For example, the Colorado River exhibited elevated levels of zinc (59-76 μg.L-1), copper (12-47 μg.L-1), lead (1.2-3.9 μg.L-1 ), iron (0.33-0.37 mg.L-1 ), and manganese (0.37-0.47 mg.L-1), while the Alajua River showed excess copper (11 μg.L-1), iron (0.61-0.72 mg.L-1), and manganese (0.62-0.98 mg.L-1). Geological factors likely contribute to the concentration of heavy metals in the upper segments of the rivers, while agricultural runoff may contribute to concentrations in the lower segments. Sediments exhibited higher average values of the Heavy Metal Evaluation Index (HEI) (20.6-26.7) compared to water samples (13.9-15.4), indicating a potential accumulation of heavy metals in the river sediments. Overall, both rivers exhibited contamination levels ranging from regular to moderate, as indicated by the calculated average Water Quality Indices (WQI), with certain areas showing slight contamination or meeting acceptable standards. These results highlight the influence of anthropogenic activities on water quality, emphasizing the necessity of continuous monitoring to assess and control their impact.